Risk and return analysis of listed multinationals on the KLSE - Heng, Helen Kooi Yee (Universiti Malaysia Sarawak (UNIMAS), 2002)
This research paper examines risk and returns characteristics of listed Multinationals and Domestic companies. Though there are abundant of documented evidence on these variables recorded by firms but there is no evidence on the same issues relating on Multinational Domestics companies on the Kuala Lumpur Stock Exchange (KLSE)